Enhancing Physical Education in Colleges of Education in the Volta Region Through Artificial Intelligence for Holistic Student Development - Ekpo, Geraldine Umoh Amba; Akude, Seyram Kafui; Agyemang, Simon Mawulorm; Azunwena, Samuel Chima; Chinda, Susan Okey (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
The study analyzed the use of Artificial Intelligence (AI) in improving physical education and wellbeing training at Volta Colleges of Education for student development. Two main research objectives and corresponding questions were addressed, guided by human resource theory. Data was collected from both primary and secondary sources using a self-developed instrument, the "Improving Physical and Wellbeing Education in Volta Colleges of Education through AI for Student Development Survey" (IPWEVCEAISDS). A sample size of 400 was selected through stratified and purposive sampling methods, with 80 respondents chosen from each of the five public Colleges in Volta. Findings indicated that AI-driven physical education is crucial for student development in Volta and contributes to regional growth. Recommendations included promoting AI-based physical education in public universities, enhancing curricula to accommodate emerging trends like skill identification and personalized learning, and training educators on AI usage for continuous improvement in teaching and learning.